Nanoscale mapping of carrier collection in single nanowire solar cells using X‐ray beam induced current. (10th December 2018) - Chayanun, Lert; Otnes, Gaute; Troian, Andrea; Hammarberg, Susanna; Salomon, Damien; Borgström, Magnus T.; Wallentin, Jesper
Abstract : Nanofocused X‐ray beam induced current (XBIC) is used to quantitatively map the spatially dependent carrier collection probability within single nanowires. Abstract : Here it is demonstrated how nanofocused X‐ray beam induced current (XBIC) can be used to quantitatively map the spatially dependent carrier collection probability within nanostructured solar cells. The photocurrent generated by a 50 nm‐diameter X‐ray beam was measured as a function of position, bias and flux in single p–i–n doped solar‐cell nanowires. The signal gathered mostly from the middle segment decays exponentially toward the p‐ and n‐segments, with a characteristic decay length that varies between 50 nm and 750 nm depending on the flux and the applied bias. The amplitude of the XBIC shows saturation at reverse bias, which indicates that most carriers are collected. At forward bias, the relevant condition for solar cells, the carrier collection is only efficient in a small region. Comparison with finite element modeling suggests that this is due to unintentional p‐doping in the middle segment. It is expected that nanofocused XBIC could be used to investigate carrier collection in a wide range of nanostructured solar cells.